Betamethasone in hernia surgery: A randomized controlled trial. (27th May 2013) - Simsa, J.; Magnusson, N.; Hedberg, M.; Lorentz, T.; Gunnarsson, U.; Sandblom, G.
Abstract Background: Post‐operative pain and nausea may be a problem in day‐case surgery. This study aims to investigate the effect of betamethasone on pain and nausea in inguinal hernia surgery. Methods: Patients aged 18–70 years scheduled for open inguinal hernia surgery at two Swedish hospitals, March 2005–December 2009, were eligible for inclusion. Patients were randomized, to either treatment with 12 mg betamethasone intravenously or placebo. Post‐operative pain was assessed using a visual analogue scale on the recovery ward, each day the first post‐operative week and at 1 month after surgery. One year after surgery, residual pain was estimated by the Inguinal Pain Questionnaire. Results: A total of 398 patients were included (21 women, 377 men). Pain at rest on the day of surgery was significantly lower in the treatment group (p = 0.012). The pain was also significantly lower in the treatment group the day after surgery (p < 0.001), but not during the remaining part of the first post‐operative week. Bleeding complications were reported by 17 patients (8.5%) in the Betamethasone group and seven (3.5%) in the placebo group (p = 0.028). One month after surgery, 21 out of 173 (12%) in the betamethasone group still had pain, compared to 33 out of 159 (21%) in the placebo arm (p = 0.049). After 1 year, no significant difference in pain was seen. Conclusion: A 12 mg betamethasone reduced pain during the first 24 h and at 1 month after inguinal hernia surgery. If combined with diclofenac, however, this dose may increase the risk for bleeding complications.